Analysis of Usury in the Modern Financial System, a Fiqh Muamalah Perspective - Nurhapidah; M. Ridwan Alwi; Nazwa Nanda Saputri; Muhamad Ibnu Malik (Konsultan Jurnal Ilmiah Indonesia, 2025)
Riba is a practice that is strictly prohibited in Islam due to its inherent elements of injustice and economic exploitation. In the context of the modern financial system, riba is often embedded in various financial instruments such as bank interest, consumer credit, and other financing products, which has led to ongoing debates among scholars and practitioners of Islamic finance. This study aims to analyze the concept of riba within the modern financial system from the perspective of fiqh muamalah. The research employs a literature review method by examining primary and secondary sources, including the Qur’an, Hadith, classical and contemporary fiqh muamalah literature, fatwas issued by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), as well as relevant academic books and journal articles. The findings indicate that, in principle, riba in modern financial practices shares the same legal cause (‘illat) as the riba prohibited in fiqh muamalah, namely the existence of predetermined additional returns without proportional risk or productive effort. However, differences in scholarly opinions persist regarding the application and boundaries of riba in modern financial products due to the complexity of today’s economic system. Therefore, strengthening the understanding of fiqh muamalah and developing Islamic financial systems are essential to provide fair, transparent, and Sharia-compliant alternatives.